Advanced three dimensional characterization of silica-based ultraporous materials. Issue 13 (26th January 2016) - Roiban, L.; Foray, G.; Rong, Q.; Perret, A.; Ihiawakrim, D.; Masenelli-Varlot, K.; Maire, E.; Yrieix, B.
Abstract : Whatever the field of application in building, transportation, packaging, etc., the energy losses must be reduced. In this context, the development of superinsulating materials is mandatory. Ultra-porous silica aerogels are good candidates. Abstract : Whatever the field of application (building, transportation, packaging, etc. ) energy losses must be reduced to meet the government target of a 40% cut in CO2 emissions. This leads to a challenge for materials scientists: designing materials with thermal conductivities lower than 0.015 W m −1 K −1 under ambient conditions. Such a low value requires reducing air molecule mobility in highly porous materials, and silica-based superinsulation materials (SIM) made of packed nanostructured silica or aerogel are good candidates for this purpose. However, the native nanostructure of silica has never been imaged or characterized up to now, making SIM optimization quite difficult. In this paper, three nanostructured commercial silica samples prepared by different synthesis methods were analysed and quantified using advanced electron tomography, N2 physisorption, mercury porosimetry and helium pycnometry. It was demonstrated that 3D images yield a much finer description of the microstructure (particle, aggregate and pore) compared to global measurements. For the samples studied, silica particle size is dependent on the synthesis method, increasing with pore diameter size. The smallest silica particles were obtained by the sol–gel method which also provides the smallest pore diameters, the smallest and rather spherical aggregates, and the lowest thermal conductivity. The pyrogenic and precipitated samples studied presented bigger silica particles with higher pore diameters and thus higher thermal conductivities. 3D image driven characterization opens up new synthesis opportunities for silica.